Channel-space endogenous anti-jamming method based on multi-reconfigurable intelligent surface - Yonggang ZHU; Yifu SUN; Fuqiang YAO; Cheng LI; Wenlong GUO; Kang AN (Tongxin xuebao)
In view of the concern that the traditional anti-jamming method based on jamming recognition is challenging to defend against both the unknown and the intelligent jamming attacks, a dynamic, heterogeneous, and redundant channel-space anti-jamming technique was proposed by adopting multiple reconfigurable intelligent surface (RIS), which facilitated the exploitation of channels’ resources for combating with the unknown jamming attacks.To elaborate, a channel-space endogenous anti-jamming method was proposed by leveraging the optimization of both the RIS’ coefficients and the multiple RIS’ on-off status.Firstly, after decoupling the tightly coupled variables, the optimal closed-form solutions of transmit precoder, RIS’ coefficients, and receive decoder could be derived under the alternative optimization framework.Then, the greedy algorithm was adopted to optimize the multiple RIS’ on-off status for obtaining better anti-jamming communications, and the convergence and the computation complexity of the proposed method was analyzed.Theoretical analysis and simulation results show that the proposed method can effectively defend against the uncertain jamming attacks.